Aetiology, diagnosis and treatment of moderate-to-severe haemoptysis in a North American academic centre. Issue 4 (19th October 2020) - Quigley, Nicholas; Gagnon, Sébastien; Fortin, Marc
Significant haemoptysis is a frightening event for patients and clinicians alike. There is a paucity of contemporary literature on the subject. A retrospective analysis of hospitalisations for haemoptysis of more than 50 mL·day −1 in a tertiary referral centre during a 5-year period was performed. Patient's characteristics, haemoptysis aetiology, management and outcome were individually recorded. The aim of this study was to detail the causes of moderate (50–200 mL·day −1 ) to severe (>200 mL·day −1 ) haemoptysis along with the diagnostic measures and treatment options used in their management in a 21st century, tertiary-care North American centre. A total of 165 hospitalisations for moderate-to-severe haemoptysis were included in the analysis. Lung cancer (30.3%) and bronchiectasis (27.9%) proved to be most frequent aetiologies. Computed tomography (CT) imaging and bronchoscopy were complementary in identifying the source of bleeding. Bronchial artery embolisation (BAE) was the most common treatment approach (61.8%) and resulted in initial bleeding control in 73.5% of cases. In-hospital mortality was 13.9%, varying from 3.3% in the moderate group to 24.7% in the severe group. Despite being the favoured approach in patients with more severe bleeding, initial BAE therapy was associated with a trend towards lower mortality compared to initial non-BAE therapy. In summary, lung cancer and bronchiectasis were the main causes of moderate-to-severe haemoptysis in our population, CT and bronchoscopy are complementary in identifying the source of bleeding, bleeding volume is associated with outcomes and BAE is a key management tool. In a contemporary North American population, lung cancer and bronchiectasis proved to be the leading causes of moderate-to-severe haemoptysis while CT and bronchoscopy appeared complementary in localising the source of bleeding https://bit.ly/2BFLvOT